Executive compensation and competition in the banking and financial sectors - Cuñat, Vicente; Guadalupe, Maria (Journal of Banking & Finance, 2009)
This paper studies the effect of product market competition on the compensation packages that firms offer to their executives. We use a panel of US executives in the 1990s and exploit two deregulation episodes in the banking and financial sectors as quasi-natural experiments. We provide difference-in-differences estimates of their effect on (1) total pay, (2) estimated fixed pay and performance-pay sensitivities, and (3) the sensitivity of stock option grants. Our results indicate that the deregulations substantially changed the level and structure of compensation: the variable components of pay increased along with performance-pay sensitivities and, at the same time, the fixed component of pay fell. The overall effect on total pay was small.